Ideological Bias in Intersemiotic News Translation of The Russo-Ukrainian War - Aarnio, Esko (My University, 2025)
This thesis examines news articles of various outlets of differing political affiliations (Russian, Ukrainian, and Western) reporting on the same issues of the Russo-Ukrainian war. The purpose of the thesis is to examine political biases found within the intersemiotic translation of said articles, especially in the form of strategic word choices and framing, utilising both news framing analysis and critical discourse analysis. Political bias is found in differing quantities within all of the articles examined in this thesis, even in those traditionally thought of as impartial and unbiased. Euphemistic and dysphemistic wording and framing in the articles mainly act to either cause indignation toward the opposing side or arouse support for the other. The findings of this thesis highlight the importance of media literacy and critical thinking.
Keywords: Political bias, news translation, Russo-Ukrainian war, news framing analysis, critical discourse analysis